Peran Budidaya Buah Naga Dalam Meningkatkan Ekonomi Masyrakat Desa Suka Ndebi Kecamatan Naman Teran Kabupaten Karo - Adris Triseptina; Nur Habibah Angkat; Rangga Heriyadi; Sarah Padillah; Siti Aisyah (Pusat Riset dan Inovasi Nasional, 2025)
Dragon fruit cultivation in Suka Ndebi Village, Naman Teran District, Karo Regency has great potential in improving the community's economy. This study aims to analyze the role of dragon fruit cultivation in enhancing rural community welfare. Using descriptive qualitative methods through interviews, observations, and documentation, it was found that dragon fruit cultivation not only contributes to income improvement but also opens new business opportunities, creates employment, and strengthens the local economy. However, challenges exist in the form of limited market access, lack of knowledge regarding modern cultivation techniques, and minimal capital support. Therefore, an integrated development strategy among farmers, government, and the private sector is essential to make dragon fruit cultivation a sustainable pillar of the village economy.